2016
DOI: 10.1108/lhs-03-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring senior nurses’ experiences of leading organizational change

Abstract: Purpose - The aim of this paper is to explore Senior nurses' experiences of leading organizational change. There is a substantial literature reporting middle-level nurse managers' experiences of change; however, there is less evidence concerning senior nurses' perspectives. In view of this, interview data collected from senior nurses, as part of a study of major organizational change, were analysed to redress this imbalance. Design/methodology/approach - In-depth semi-structured interviews (n = 14) were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…Ancak, literatürde üst düzey yönetici hemşirelerin değişime liderlik etmeleri, değişime aktif şekilde katılmaları, diğer hemşirelerin endişelerini paylaşmaları ve onların da değişim sürecine katılımını sağlamaları gerektiği ifade edilmektedir. [20] Sonuç olarak hemşireler değişimin sağladığı fırsatlarından yararlanamamış ve aynı zamanda değişimin sonuçlarından olumsuz etkilenmiştir. [17][18][19][20][21] Bütün bu faktörler hemşirelerin değişime yönelik genel tutumlarını olumsuz yönde etkilemiş olabilir.…”
Section: Hemşirelerin Değişime Yönelik Tutumları Ile Beş Faktör Kişilunclassified
“…Ancak, literatürde üst düzey yönetici hemşirelerin değişime liderlik etmeleri, değişime aktif şekilde katılmaları, diğer hemşirelerin endişelerini paylaşmaları ve onların da değişim sürecine katılımını sağlamaları gerektiği ifade edilmektedir. [20] Sonuç olarak hemşireler değişimin sağladığı fırsatlarından yararlanamamış ve aynı zamanda değişimin sonuçlarından olumsuz etkilenmiştir. [17][18][19][20][21] Bütün bu faktörler hemşirelerin değişime yönelik genel tutumlarını olumsuz yönde etkilemiş olabilir.…”
Section: Hemşirelerin Değişime Yönelik Tutumları Ile Beş Faktör Kişilunclassified
“…Leading change is viewed as a part of everyday practice for leaders and managers, as they are called on to transform the system (Ministerial Review Group, 2009). This is despite the evidence of the increased workload associated with leading improvement initiatives (Hayes et al, 2015), and how a target-driven health system can mean that some leaders have no time for strategic thinking and planning (Boyal and Hewison 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of leadership within organizational change models in healthcare organizations continues to be discussed. Some studies regarding change leadership specifically have been reported recently (10). Øygarden et al (11) referenced Yukl's model of change-oriented leadership behaviors as including monitoring and interpreting the environment, envisioning new possibilities for the organization, explaining the need for change, suggesting new and creative solutions and experimenting with new approaches for achieving objectives, taking a long-term perspective on problems and opportunities and negotiating for support from other actors on behalf of the department.…”
Section: Introductionmentioning
confidence: 99%